2022
DOI: 10.1155/2022/5078134
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Method of Coal Dust Explosion Flame Propagation Characteristics Based on Principal Component Analysis and BP Neural Network

Abstract: To study the flame propagation characteristics of coal dust explosion, principal component analysis and BP neural network are used to predict the farthest distance and the maximum speed of flame propagation. Among the eight influencing factors of flame propagation characteristics, three principal components are extracted and named “the factor of volatility,” “the factor of intermediate diameter,” and “the factor of environmental temperature.” By using BP neural network, it is found that the minimum prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In previous research, the author of this paper found that different factors have different effects on coal dust ignition, and too many factors affecting coal dust explosion are one of the important reasons for the di culty in preventing and controlling explosions [29][30][31][32], the author has clari ed the formation process and in uencing factors of the secondary explosion of coal dust [33]. In order to further study the suppression effect of different types of inert dust on coal dust explosion pressure, in this paper, the spherical explosion apparatus was used to test the explosion pressure, and the micron-sized explosive coking coal dust was used as the experimental sample.…”
Section: Introductionmentioning
confidence: 87%
“…In previous research, the author of this paper found that different factors have different effects on coal dust ignition, and too many factors affecting coal dust explosion are one of the important reasons for the di culty in preventing and controlling explosions [29][30][31][32], the author has clari ed the formation process and in uencing factors of the secondary explosion of coal dust [33]. In order to further study the suppression effect of different types of inert dust on coal dust explosion pressure, in this paper, the spherical explosion apparatus was used to test the explosion pressure, and the micron-sized explosive coking coal dust was used as the experimental sample.…”
Section: Introductionmentioning
confidence: 87%
“…In previous research, the author of this paper revealed the ignition characteristics and flame propagation process of different types of coal dust cloud under different conditions 29 32 and also discovered the explosion characteristics of deposited coal dust driven by airflow carrying coal dust and the suppression effect of inert dust CaCO 3 on explosion. 33 Using inert dust is a very economical and effective method to control coal dust explosion.…”
Section: Introductionmentioning
confidence: 90%
“…Te physical and structural drawings of the experimental device for the coal dust explosion fame test are shown in the literature [35]. Te device mainly includes a glass tube system, a dust spraying system, an ignition system, a highspeed camera system, a data acquisition system, and a tube purging system.…”
Section: Experimental Device Of Coal Dust Explosion Flamementioning
confidence: 99%
“…Terefore, based on the above analysis, this paper will take nonstick coal as the research object, use SiO 2 , KCl, and NH 4 H 2 PO 4 as the explosion suppressants, and use the explosion fame and pressure to characterize the explosion intensity to study the inhibition of three kinds of explosion suppressants on the explosion intensity of nonstick coal dust. In the previous research, the author obtained the ignition characteristics of the coal dust cloud and the propagation process of the explosion fame, as well as obtained the fame characteristics of the coal dust explosion space and the concentration distribution of gas products generated by the numerical method [32][33][34][35][36]. In this paper, the author will further discuss the suppression efect of SiO 2 , KCl, and NH 4 H 2 PO 4 on the fame and pressure of a nonstick coal dust explosion.…”
Section: Introductionmentioning
confidence: 99%